The banking bailout of the subprime crisis: size and effects - Fratianni, Michele; Marchionne, Francesco (PSL Quarterly Review, 2010)
This paper examines government policies aimed at rescuing banks from the effects of the great financial crisis of 2007-2009. To delimit the scope of the analysis, we concentrate on the fiscal side of interventions and ignore, by design, the monetary policy reaction to the crisis. The policy response to the subprime crisis started in earnest after Lehman’s failure in mid September 2008, accelerated after February 2009, and has become very large by September 2009. Governments have relied on a portfolio of intervention tools, but the biggest commitments and outlays have been in the form of debt and asset guarantees, while purchases of bad assets have been very limited. We employ event study methodology to estimate the benefits of government interventions on banks and their shareholders. Announcements directed at the banking system as a whole (general) and at specific banks (specific) were priced by the markets as cumulative abnormal rates of return over the selected window periods. General announcements tend to be associated with positive cumulative abnormal returns and specific announcements with negative ones. General announcements exert cross-area spillovers but are perceived by the home-country banks as subsidies boosting the competitive advantage of foreign banks. Specific announcements exert spillovers on other banks. Our results are also sensitive to the information environment. Specific announcements tend to exert a positive impact on rates of return in the pre-crisis sub-period, when announcements are few and markets have relative confidence in the “normal” information flow. The opposite takes place in the turbulent crisis sub-period when announcements are the order of the day and markets mistrust the “normal” information flow. These results appear consistent with the observed reluctance of individual institutions to come forth with requests for public assistance. JEL Codes: G01, G21, N20